High efficiency, site-specific excision of a marker gene by the phage P1 cre–loxP system in the yellow fever mosquito, Aedes aegypti - Jasinskiene, Nijole (Oxford University Press, 2003)
The excision of specific DNA sequences from integrated transgenes in insects permits the dissection in situ of structural elements that may be important in controlling gene expression. Furthermore, manipulation of potential control elements in the context of a single integration site mitigates against insertion site influences of the surrounding genome. The cre–loxP site-specific recombination system has been used successfully to remove a marker gene from transgenic yellow fever mosquitoes, Aedes aegypti. A total of 33.3% of all fertile families resulting from excision protocols showed evidence of cre–loxP-mediated site-specific excision. Excision frequencies were as high as 99.4% within individual families. The cre recombinase was shown to precisely recognize loxP sites in the mosquito genome and catalyze excision. Similar experiments with the FLP/FRT site-specific recombination system failed to demonstrate excision of the marker gene from the mosquito chromosomes.